2014
DOI: 10.1016/j.jclinepi.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

After adjusting for bias in meta-analysis seasonal influenza vaccine remains effective in community-dwelling elderly

Abstract: This case study showed that after addressing potential biases influenza vaccine was still estimated effective in preventing hospitalization from influenza and/or pneumonia and all-cause mortality. Increasing the number of assessors and incorporating empirical evidence might improve the new bias-adjustment method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Ortiz and collaborators [32] Hospital 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) Limitation of therapy in-hospital, n (%) DNR 72 (11.9) WH/WD 57 (9.4) about 28,000 adults are hospitalized for influenza-associated critical illness in the USA annually. A recent biasadjusted meta-analysis [33] confirmed that influenza vaccine was effective in preventing hospitalization from influenza and/or pneumonia and all-cause mortality in community-dwelling elderly. However, the evidence to support risk factors for influenza-related complications is still low and adequately powered studies are needed to address this issue [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz and collaborators [32] Hospital 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) Limitation of therapy in-hospital, n (%) DNR 72 (11.9) WH/WD 57 (9.4) about 28,000 adults are hospitalized for influenza-associated critical illness in the USA annually. A recent biasadjusted meta-analysis [33] confirmed that influenza vaccine was effective in preventing hospitalization from influenza and/or pneumonia and all-cause mortality in community-dwelling elderly. However, the evidence to support risk factors for influenza-related complications is still low and adequately powered studies are needed to address this issue [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Our review suggests that the 43–58% protection by the vaccine against laboratory‐confirmed influenza in the elderly was slightly lower in the tropics and subtropics compared to 50–77% protection seen in Europe, United States and other developed countries 61, 62. The protection in children (range 20–77%) and in healthy adults (range 50–59%) seen in the tropics and subtropics was comparable with that seen in developed countries 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of pneumococcal pneumonia has been shown to increase following influenza virus infection in the elderly [63]. Although the effectiveness, in relation to hospitalization and mortality rates, of the influenza vaccine alone in elderly patients has not been assessed by meta-analysis in the previous studies [64,65], a combined vaccination of the influenza vaccine and PPV is thought to be effective in these patients [66]. Inoculation with both these vaccines may have an additive effect in reducing pneumonia hospitalization in elderly patients with a risk of ASP [67].…”
Section: Pharmacologic Approaches For Dysphagia and Upper Airway Manamentioning
confidence: 99%